1994
DOI: 10.1007/bf00196638
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of flowering and fruiting on individual trees over 3 years and their effects on subsequent crown condition

Abstract: Summary. The level of fruiting in four forest trees species(Picea sitchensis, P. abies, Pinus sylvestris and Fagus sylvatica) was monitored in Great Britain over the period 1989-1991. In addition, assessments of crown transparency were available for many of the trees for 1987 and 1988. The monitoring period encompassed severe summer droughts in 1989 and 1990, with wetter conditions in 1991. Variations in the level of fruiting in spruce and beech (Fagus sylvatica L.) were seen, with a marked peak in 1990. No pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 46 publications
5
27
0
3
Order By: Relevance
“…Seed production may be increased by drought, but often drops during the two to three years following a drought. Such an observation was reported for beech after the 1989 drought in Britain [66,70]. More recently in Germany, Eichhorn et al [43] showed that over 80% of the beech trees exhibited a heavy mast production during 2004, which was the highest figure since 1990.…”
Section: Delayed Effects Of Drought On Wood Leaf and Fruit Productionmentioning
confidence: 57%
See 1 more Smart Citation
“…Seed production may be increased by drought, but often drops during the two to three years following a drought. Such an observation was reported for beech after the 1989 drought in Britain [66,70]. More recently in Germany, Eichhorn et al [43] showed that over 80% of the beech trees exhibited a heavy mast production during 2004, which was the highest figure since 1990.…”
Section: Delayed Effects Of Drought On Wood Leaf and Fruit Productionmentioning
confidence: 57%
“…As a consequence of higher mast production, leaf area is reduced and crown transparency increases. However, it is not clear whether the process that triggers the drought-induced flowering and seed production also triggers the dieback or whether the relationship between dieback and fruit production is directly causal [70]. Controversial observations were reported for beech vs. spruce or Scots pine.…”
Section: Delayed Effects Of Drought On Wood Leaf and Fruit Productionmentioning
confidence: 99%
“…The latter also applies Fagus (Innes 1994) and may apply to Quercus and Tilia as well. Positive correlations with winter or spring temperatures have been observed for Quercus in Poland and the Czech mountains (van der Knaap et al 2010, this volume).…”
Section: Effect Of Temperatures In Flowering Yearmentioning
confidence: 99%
“…The position within the canopy affects holm oak phenology and flowering (Innes, 1994;Nuzzo et al, 1997;La Mantia et al, 2003). Peter and Harrington (2002) found higher acorn production in the top half of the canopy in Quercus alba stands.…”
Section: Other Factors Affecting Acorn Productionmentioning
confidence: 99%